Bioinspired and bristled microparticles for ultrasensitive pressure and strain sensors - Bing Yin (Nature Portfolio, 2018)
The potential of electromechanical sensors has been limited by low volumetric density in sensing sites. Here, the authors demonstrate ultrasensitive pressure and strain sensors using ZnO microparticles that have high-aspect ratio and high-density nanostructured spines mimicking bristles in insects.